1997
DOI: 10.1002/etc.5620160234
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that variability in ambient fathead minnow short‐term chronic tests is due to pathogenic infection

Abstract: Abstract-An examination of results from ambient fathead minnow subchronic toxicity tests identified a common characteristic of the tests, which manifests itself as a large among-replicate and between-test variance in survival. The unusual replicate-specific mortality in tests with ambient water appears to be due to pathogenic bacteria or fungi. This finding is based on the following facts: a comparison of survival among replicates in effluents and ambient waters showed that when mean survival was low (40-70%),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1997
1997
2000
2000

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
(27 reference statements)
1
13
0
Order By: Relevance
“…Sea urchin fertilization tests can be highly variable depending on geographic location, apparently related to ambient temperatures [46]. Pathogenic infection can cause variability in fathead minnow tests [47]. Hence, the original C. dubia toxicity test was rigorously standardized (compare Mount and Norberg [29] with current test methods such as those of the Canadian Environmental Protection Service [48] and the U.S. EPA [49]).…”
Section: Usefulnessmentioning
confidence: 99%
“…Sea urchin fertilization tests can be highly variable depending on geographic location, apparently related to ambient temperatures [46]. Pathogenic infection can cause variability in fathead minnow tests [47]. Hence, the original C. dubia toxicity test was rigorously standardized (compare Mount and Norberg [29] with current test methods such as those of the Canadian Environmental Protection Service [48] and the U.S. EPA [49]).…”
Section: Usefulnessmentioning
confidence: 99%
“…Survival of fathead minnows in all river water samples was significantly less in August than in May or October ( p lt; 0.05). The suggestion has been made that excessive mortality of larval minnows during ambient toxicity tests may be caused by bacteria, which cause infections and mortality during the tests [31]. The average temperature of the samples collected in August was approximately 22°C, compared to temperatures of 2 to 5°C in May and 6 to 8°C in October.…”
Section: Discussionmentioning
confidence: 99%
“…Test interference attributed to pathogenic organisms has been reported when conducting chronic P. promelas WET tests per standard methodology [1,2]. One study [3] reported a mean survival of ≤60% in P. promelas chronic toxicity tests on ambient water. High among‐replicate variability for survival also was noted in the study.…”
Section: Introductionmentioning
confidence: 99%
“…Survival of P. promelas was substantially increased when the samples were exposed to UV light and when the larva were evaluated individually as opposed to the standard 10 per replicate. The authors concluded that their results were best explained by naturally occurring pathogens present in the ambient waters [3]. Other investigators also reported anomalous test results using P. promelas that were believed to be due to a naturally occurring biological interference characterized by filamentous growths on the larvae.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation